Investigation of some parasitic, bacterial and BVDV agents in dairy cows based on a past of abortions - Fatma S. Aktürk; Yakup S. Orta; Sibel Yaman; Ozan Koçlu; Kamil Atlı; Dilek Öztürk; Sevinç Kant; Mehmet Kale (Pesquisa Veterinária Brasileira)
ABSTRACT: Blood samples were taken from 94 dairy cows based on a past of abortions (4th-7th months) in four different farms in Burdur province. The presence of Chlamydophila abortus (Antibody = Ab), Coxiella burnetti (Ab), Sarcocystis spp. (Ab), Neospora caninum (Ab) and bovine viral diarrhea virus (BVDV) (Antigen = Ag) were investigated in the collected blood samples. While seropositivity was determined for C. abortus, C. burnetti and N. caninum in the samples, BVDV was detected positive in the same samples. No samples were detected seropositive for Sarcocystis spp. (Ab). N. caninum showed the highest seropositivity in the samples tested, whereas C. burnetti had the lowest. When we looked at the mixed distribution of the factors in the positive animals, C. abortus + N. caninum was found to be the highest, and C. burnetti + N. caninum was the lowest. As a result of the study, it was determined that N. caninum was the most common abortion factor in cattle that had abortions between 4-7 months, and BVDV, C. abortus and C. burnetti, respectively, could also cause abortion. The high level of N. caninum indicates that canes and underground spring waters around the farms may be important reservoirs.